2009
DOI: 10.1016/j.micpath.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in human neutrophils by Mycobacterium tuberculosis is dependent on mature bacterial lipoproteins

Abstract: Modulation of immune cell apoptosis is a key evasion strategy utilized by Mycobacterium tuberculosis (Mtb). To be able to multiply within macrophages, the bacterium delays apoptosis and down-regulates pro-inflammatory activation in these cells, whereas apoptosis is rapidly induced in the potently bactericidal neutrophils. Initial host-pathogen interactions between neutrophils and Mtb, subsequently leading to apoptosis, need to be investigated to understand the early features during Mtb infections. Opsonized Mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Persson et al [21] also showed that an Mtb lspA-/- mutant lacking the 19-kDa lipoprotein did not induce apoptosis in neutrophils. Using this Mtb mutant, we investigated whether apoptosis was a prerequisite for Mtb-induced NET formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Persson et al [21] also showed that an Mtb lspA-/- mutant lacking the 19-kDa lipoprotein did not induce apoptosis in neutrophils. Using this Mtb mutant, we investigated whether apoptosis was a prerequisite for Mtb-induced NET formation.…”
Section: Resultsmentioning
confidence: 99%
“…Considering our previous observations that Mtb-induced apoptotic neutrophils can induce a proinflammatory activation of macrophages [18,19,20,21], we asked whether NETs could mediate this activating signal to macrophages. Macrophages and neutrophils coexist at the inflammation site and work in concert to remove pathogens [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike macrophages, neutrophils are prone to undergo apoptosis upon infection with wild type M. tuberculosis expressing the 19 kDa lipoprotein (232)(233). Subsequent uptake of apoptotic neutrophils or macrophages by other phagocytes, primarily macrophages, plays a role in infections and helps modulate the immune response.…”
Section: Efferocytosismentioning
confidence: 99%
“…Uptake of mycobacteria by neutrophils leads to killing of the bacteria as well as induction of apoptosis. However, non-infected neutrophils at the site of infection are still shortlived cells and undergo apoptosis spontaneously within 24 hours after leaving circulation (231)(232). After induction of apoptosis, the apoptotic neutrophils are recognized and cleared by other adjacent phagocytes.…”
Section: Paper IVmentioning
confidence: 99%